Offshoring and ICT: Evidence for German manufacturing and service firms - Fabienne Rasel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this paper, I analyse the relationship between offshoring and ICT at the firm level differentiating between manufacturing and services. Using firm-level data from the manufacturing and service sector in Germany and a broad range of ICT measures, overall, the results reveal a positive relationship between offshoring and ICT. Thus, they support the argument that ICT might be relevant for offshoring. Controlling for other firm characteristics, software to coordinate and to manage the supply chain increases the offshoring probability, in particular for manufacturing firms. For service firms, also general enterprise software and e-commerce purchases from suppliers make offshoring more likely. Labour productivity and the realisation of a product innovation are significantly and positively linked to offshoring for firms from both sectors. This finding confirms the productivity advantage of offshoring in comparison to non-offshoring firms that is stated in the literature.
Keywords: D22; L23; F14; 330; Offshoring; information and communication technologies; firm-level analysis